2012
DOI: 10.3141/2299-01
|View full text |Cite
|
Sign up to set email alerts
|

Documenting Targeted Behaviors Associated with Pedestrian Safety

Abstract: The purpose of this study was to provide an exploratory analysis of the proportion of pedestrians, bicyclists, and drivers exhibiting four specific behaviors at 12 intersections near transit stations in the San Francisco Bay Area of California. Those target behaviors were (a) pedestrians crossing a roadway while using a mobile device, such as a cell phone; (b) pedestrians crossing a signalized intersection against a red light; (c) bicyclists running a red light at a signalized intersection; and (d) automobiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
3
11
1
Order By: Relevance
“…The observed rates of distracted walking are consistent with those reported by others 10 11. The high prevalence of these behaviours may pose emerging injury risks in urban areas as mobile technology increases in popularity1 2 and increasing proportions of the US14 15 and global16 population migrate to urban areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed rates of distracted walking are consistent with those reported by others 10 11. The high prevalence of these behaviours may pose emerging injury risks in urban areas as mobile technology increases in popularity1 2 and increasing proportions of the US14 15 and global16 population migrate to urban areas.…”
Section: Discussionsupporting
confidence: 88%
“…An Australian study revealed that male pedestrians talking on a mobile phone crossed more slowly than matched controls at ‘unsignalised’ crosswalks, and that females using phones not only crossed streets more slowly but were also less likely to look for traffic before or while crossing 9. A study of pedestrian behaviour at 12 intersections in San Francisco found that up to 18% of pedestrians were using a mobile device when crossing the street 10. In another recent study in Seattle that included observations of over 1100 pedestrians crossing at 20 high-risk intersections, almost 30% engaged in at least one distracting behaviour, including text messaging, listening to music or talking on a phone 11.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of models and methods for evaluating pedestrian traffic conflicts and predicting collisions have been published (4)(5)(6). Similarly, considerable research exists on the evaluation of the built environment for pedestrian safety and comfort, in particular on the relationship between infrastructure improvements and pedestrian behaviors (7)(8)(9). Although the efficacy of enforcement programs aimed at improving pedestrian behavior has been demonstrated (8,9), researchers have found that in many cases design interventions are an essential prerequisite to changing unsafe user behaviors (7,8).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Similarly, considerable research exists on the evaluation of the built environment for pedestrian safety and comfort, in particular on the relationship between infrastructure improvements and pedestrian behaviors (7)(8)(9). Although the efficacy of enforcement programs aimed at improving pedestrian behavior has been demonstrated (8,9), researchers have found that in many cases design interventions are an essential prerequisite to changing unsafe user behaviors (7,8). Because specific countermeasures that improve pedestrian safety outcomes are well outlined in the literature, they were discussed minimally in this research, although the finding that infrastructure improvement should be prioritized was an underlying assumption of the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This section discusses the literature available on pedestrian-vehicle interactions. Cooper and Schneider (2012) examined the frequency of specific behaviors at intersections near transit facilities in the Bay Area of San Francisco. The target behaviors were: (a) pedestrians crossing the roadway while using a mobile device, such as a cell phone, (b) pedestrians crossing a signalized intersection against a red light, (c) bicyclists running a red light at a signalized intersection, and (d) motorists turning right on red without stopping.…”
Section: Pedestrian-vehicle Interactionmentioning
confidence: 99%